Strategi Tokoh Agama dalam Membangun Kerukunan Antarumat Beragama Indonesia - Artariah Artariah (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
In this paper, the author discusses inter-religious harmony in Indonesia with a focus on the strategic role of religious leaders in building brotherhood. Indonesia, as a country with rich religious diversity, faces challenges in maintaining harmony amidst complex societal dynamics. Through qualitative analysis by examining literature from various sources, this paper identifies concrete strategies that have been implemented by religious figures. Religious figures have a central role as spiritual leaders, spiritual advisors, and religious teachers, significantly influencing religious and social life. Although Indonesia is known as a tolerant country, several challenges such as social conflict, religious polarization, and intolerance are still issues. The concrete strategies proposed involve interfaith dialog, joint social activities, educational initiatives, communication strategies, and strengthening nationalistic insights. These efforts are expected to strengthen interfaith brotherhood and maintain harmony in the future. The results indicate that religious leaders can serve as agents of peace and tolerance, but they are also faced with challenges such as conflict, politicization of religion, and difficulties in interfaith communication and dialogue.